Peningkatkan Prestasi Belajar Peserta Didik dengan Penerapan Model Pembelajaran Kooperatif Formulate, Share, Listen and Create (FSLC) pada Pokok Bahasan Kesetimbangan Ion dan pH Larutan Garam di Kelas XI MIA SMA Negeri 4 Pekanbaru - Ariani, Desy; Azmi, Johni; Linda, Roza (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
Improving student achievement by applying the cooperative learning model Formulate, Share, Listen and Create (FSLC) on the subject of ionic equilibrium on pH of salt solution in classXI MIA SMA Negeri 4 Pekanbaru with experimental research method design randomized control groupcpretest-posttesteagainst two homogeneous classes. The samples of the study were students in class XI MIA 7 and XI MIA 8. Hypothesis testing using the t-test showed that there was a difference in the improvement in learning achievement betweensthe control class and thesexperimental class, the value of tcount> ttable was 5.66> 1.67 at dk = 36 + 35 - 2 = 69. The results show that the applications of the FSLC cooperative learningsmodel can improve student achievement on the subject of ionic equilibrium and pH of salt solution with the category of increasing learning achievement based on and N-gain score of 0.75 which is in the high category. Keywords: FSLC Cooperative Learning, Learning Achievement, Ion Balance and Salt Solution pH